Pola Komunikasi Pelestarian Seni dan Budaya Masyarakat Akur Sunda Wiwitan di Era Globalisasi - Fadilah, Wafa; Latifah, Hanny; Raturahmi, Leadya (LPPM Stikosa - AWS, 2023)
As time goes by, even though there are positive impacts, we also have to be aware of the negative impacts that can threaten existing local culture. However, in the Akur Sunda Wiwitan community, they have a way to maintain their local beliefs, customs and culture amidst rapid technological advances. This research aims to reveal how the Akur Sunda Wiwitan people use communication patterns as a tool to maintain the arts and culture that have been passed down from one generation to the next. This research uses qualitative research methods with a constructivist approach, based on ethnographic communication theory. The data in this research was obtained through observation, in-depth interviews and documentation. The data analysis process follows the Miles and Huberman model, which includes the steps of data collection, data reduction, data presentation, and drawing conclusions. The results of the research are presented in the form of a qualitative description, namely explaining the communication patterns used by the Akur Sunda Wiwitan community in written form. This research focuses on two interesting activities studied, namely communication patterns that emerge in Nonoman routine collections and Taman Atikan activities. The communication carried out in these two activities are uses verbal and non-verbal communication. In the Nonoman group, there is a two-way communication pattern, while in Taman Atikan activities, there is a circular communication pattern. In these two communication patterns, the communicator and the communicant can directly interact with each other.